Self-service token vending machines: are train commuters satisfied and continue to use them? / Muhammad Farhan Mohd Halim, Zurinawati Mohi and Raja Puteri Saadiah Raja Abdullah - Mohd Halim, Muhammad Farhan; Mohi, Zurinawati; Raja Abdullah, Raja Puteri Saadiah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
Global acceptance of self-service technology (SST) is derived from the retail sector. SST is designed to enhance the services and is installed in many stations to reduce the waiting time when getting a train ticket. After exploratory factor analysis, five dimensions were formed: machine performance, self-control, reliability, perceived ease of use, and commuters' emotion. Based on the regression analysis result, it can be concluded that the three dimensions, i.e., machine performance, reliability, and self-control, are able to influence the experience of the train commuters directly; hence, it can be a blueprint for the service provider to ensure all aspects of their service will always be in good condition. Thus, the study has proven that train commuters' experience might influence the continuation intention mediating for two dimensions of token vending machine, i.e., machine performance and self-control.